2007
DOI: 10.1007/s00265-007-0480-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the mating system from phenotypic correlations between life-history and sperm quality traits in the Alpine whitefish Coregonus zugensis

Abstract: The mating behavior and reproductive strategies of Alpine whitefish like Coregonus zugensis (Nüsslin) are poorly understood, probably because they spawn in deep water where direct observations are difficult. In this study, we interpret life-history and sperm quality traits of fish that we caught from their spawning place. We found that males invest heavily into gonadal tissue (up to 5.6% of their body weight), which is, in comparison to other fish, consistent with external fertilization, distinct pairing and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
(58 reference statements)
1
22
1
1
Order By: Relevance
“…In the sample used for the present study, individuals with high fluctuating asymmetry and with at least some types of gonadal alterations were found to have faster sperm than other males ). Thus, and because increased sperm velocity may compensate for social, genetic and/or phenotypic disadvantages (Taborsky 1998, Rudolfsen et al 2006, Rudolfsen et al 2008, gonadal malformations may also be regarded as an indicator of genetic quality and as another phenotypic expression of developmental instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sample used for the present study, individuals with high fluctuating asymmetry and with at least some types of gonadal alterations were found to have faster sperm than other males ). Thus, and because increased sperm velocity may compensate for social, genetic and/or phenotypic disadvantages (Taborsky 1998, Rudolfsen et al 2006, Rudolfsen et al 2008, gonadal malformations may also be regarded as an indicator of genetic quality and as another phenotypic expression of developmental instability.…”
Section: Introductionmentioning
confidence: 99%
“…In the sample used for the present study, individuals with high fluctuating asymmetry and with at least some types of gonadal alterations were found to have faster sperm than other males ). Thus, and because increased sperm velocity may compensate for social, genetic and/or phenotypic disadvantages (Taborsky 1998, Rudolfsen et al 2006, Rudolfsen et al 2008, gonadal malformations may also be regarded as an indicator of genetic quality and as another phenotypic expression of developmental instability.Here we tested whether there is a link between the occurrence of gonadal alterations and genetic quality by monitoring an important aspect of offspring fitness, namely embryo viability from fertilization until hatching. If the aberrant development of gonadal tissues is a phenotypic expression of reduced genetic quality, parental individuals displaying gonadal alterations would be expected to sire embryos of reduced viability.…”
mentioning
confidence: 99%
“…Thus, variation in viability appears to be shaped by selection and probably plays a key role in how insect mating systems evolve. Intraspecific variation in sperm viability may be the result of male physiological condition [3,4], male genotype [5], meiotic drive [2], or female mating history [6]. Recent work in vertebrates also suggests that variation may be influenced by a male's current pathogen load [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the primary function of breeding tubercles in whitefish is to maintain contact between individuals during spawning, although the conspicuous white colour and hardness of these ornaments may enable tubercles to be used also as visual and tactile signals (Wiley & Collette, 1970). Even though it is not known whether these tubercles are costly to produce ; but see also Kortet et al, 2003), previous studies have demonstrated that the size and/or number of the breeding tubercles are linked to individual condition (Wedekind, 1992;Rudolfsen et al, 2008), parasite resistance (Kortet et al, 2004b) and male dominance (Kortet et al, 2004a). In addition, Wedekind et al (2001) demonstrated strong maternal and paternal effects in egg mortality of whitefish, and reported a negative association between the size of male breeding tubercles and embryonic mortality (i.e.…”
Section: Introductionmentioning
confidence: 94%